Between Bolivian Cinema during the 60’s and the Novel Promoting the Indigenous Cause: a case of Andean Aesthetic Transculturation - Sanjinés C., Javier (Procesos. Revista Ecuatoriana de Historia, 2015)
This article is an exercise in cultural history that explores the conflictive relationship between the cinematographic work by Bolivian director Jorge Sanjinés involving the Ukamau group developed in the 70’s and the Andean novel that showcased the Indigenous cause written several decades before concerning issues of indigenous representation and its place in the local community. From this perspective, this article analyzes the complex interaction between learned culture, film-making and local construction in Bolivia. This study considers modernizing historical context undertaken by the Revolution of 1952 and the subsequent happenings that occurred during this political and social process essential to that Andean country situating the aesthetic and political challenges that Jorge Sanjinés’ work had to have faced.